Short communication: Disparities in early luteal phase progesterone concentrations between repeat breeder and fertile Aceh cattle - CUT NILA THASMI; UMAR PUTEH HAFIZUDDIN; HUSNURRIZAL HUSNURRIZAL; TONGKU NIZWAN SIREGAR; HERRIALFIAN HERRIALFIAN; AMALIA SUTRIANA; ROSMAIDAR ROSMAIDAR; FARAH FARIDA HANUM; GHOLIB GHOLIB; ARMAN SAYUTI; YUSMADI YUSMADI; RINA AULIA BARUS; MOHAMMED AHMED ELSHAREF ABDELBAGI (Asian Journal of Agriculture, 2025)
Abstract. Thasmi CN, Hafizuddin UP, Husnurrizal, Siregar TN, Herrialfian, Sutriana A, Rosmaidar, Hanum FF, Gholib, Sayuti A, Yusmadi, Barus RA, Abdelbagi MAE. 2025. Short communication: Disparities in early luteal phase progesterone concentrations between repeat breeder and fertile Aceh cattle. Asian J Agric 9: 854-860. Repeat breeding remains a major reproductive constraint in cattle, often associated with altered luteal function and inadequate progesterone production during early estrus cycles. Understanding hormonal differences between fertile and repeat breeder cows is essential for improving reproductive efficiency in Aceh cattle (Bos indicus). This study aimed to investigate disparities in progesterone concentrations during the early luteal phase between repeat breeder and fertile Aceh cows. Six multiparous Aceh cows, aged 3-5 years and weighing 150-250 kg, were selected as study subjects. The cows were divided into two groups: repeat breeders (n=3) and fertile cows (n=3). To ensure synchronized estrus timing, all cows received 5 ml PGF2α (Enzaprost®-T, Dinoprost 5 mg) using the by double injection method. Estrus detection was performed following PGF2α injection in the morning and afternoon. Blood samples were collected on days 3 and 6 post-estrus for progesterone analysis. Progesterone concentrations were determined measured using the Enzyme-Linked Immunosorbent Assay (ELISA) method, and the data were analyzed using the Mann-Whitney U test. Results indicated that progesterone concentrations on days 3 and 6 were 5.68±4.98 and 6.61±3.04 ng/mL in fertile cows, whereas in repeat breeder cows, the concentrations were only 0.35±0.07 and 2.74±0.58 ng/mL, respectively. A significant difference in progesterone concentration was observed on day 3 between the two groups (p < 0.05). The conclusion indicates that repeat breeder Aceh cows exhibit lower progesterone concentrations during the early luteal phase compared to fertile cows. These findings contribute significantly to the understanding of hormonal differences between the two groups, which may serve as a foundation for developing more effective and sustainable breeding strategies.